2010
DOI: 10.3758/mc.38.6.713
|View full text |Cite
|
Sign up to set email alerts
|

Shared spatial representations for physical locations and location words in bilinguals’ primary language

Abstract: The cognitive processing of persons fluent in two languages has received considerable research interest, resulting in an entire handbook devoted to the topic (Kroll & De Groot, 2005). Lexical decision and naming tasks, often coupled with priming procedures, have been used to assess how meaning is represented in the first and second languages. A common finding is that of processing asymmetry, in which the first language tends to dominate the second (e.g., Kroll & Stewart, 1994). For example, when a semantically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…This finding led them to propose that the BA might stem from a general-executive control superior ability, which was referred to as the BEPA hypothesis. The results of the present study concerning global RTs showed that bilinguals and monolinguals were equally fast across tasks, at odds with previous studies showing that bilinguals outperform monolinguals (Kousaie & Phillips, 2017;Vu et al, 2010). However, this outcome is in line with the conclusions of the latest review by Hilchey et al (2015), who revealed that the pattern of BEPA results has shifted from robust to uncommon.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…This finding led them to propose that the BA might stem from a general-executive control superior ability, which was referred to as the BEPA hypothesis. The results of the present study concerning global RTs showed that bilinguals and monolinguals were equally fast across tasks, at odds with previous studies showing that bilinguals outperform monolinguals (Kousaie & Phillips, 2017;Vu et al, 2010). However, this outcome is in line with the conclusions of the latest review by Hilchey et al (2015), who revealed that the pattern of BEPA results has shifted from robust to uncommon.…”
Section: Discussioncontrasting
confidence: 85%
“…NgF) as compared to bilinguals, and contradicting the predictions of the BEPA hypothesis. As far as we know, only two previous studies have reported similar results (Morales et al, 2013;Vu et al, 2010), and none did so using either flanker or no-go flanker paradigms. In fact, in studies with comparable designs to the current one, results show the opposite pattern (Emmorey et al, 2008;Jiao et al, 2019;Luk et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Both location words and arrows yield S-R mapping effects when the location information conveyed by them is relevant (Wang & Proctor, 1996) and Simon effects when it is irrelevant (Proctor & Vu, 2002). Moreover, the locationbased Simon effect is eliminated when location-based Simon task trials are intermixed with ones in which participants respond to the words left and right with incompatibly mapped keypresses (Notebaert et al, 2007;Proctor et al, 2000;Vu, Ngo, Minakata, & Proctor, 2010).…”
Section: Mode-specific or Shared Mechanismmentioning
confidence: 98%